2014
DOI: 10.1038/bjc.2014.333
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to diagnose ovarian cancer: new evidence from phase 3 of the multicentre international IOTA study

Abstract: Background:To compare different ultrasound-based international ovarian tumour analysis (IOTA) strategies and risk of malignancy index (RMI) for ovarian cancer diagnosis using a meta-analysis approach of centre-specific data from IOTA3.Methods:This prospective multicentre diagnostic accuracy study included 2403 patients with 1423 benign and 980 malignant adnexal masses from 2009 until 2012. All patients underwent standardised transvaginal ultrasonography. Test performance of RMI, subjective assessment (SA) of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 38 publications
7
103
2
1
Order By: Relevance
“…This performance could be further improved by tutoring from medical practitioners who are experts in gynecological ultrasound [16]. M a n u s c r i p t Although this was a small series, the results were consistent with larger studies that use Descriptors + Rules + Expert: Sayasneh et al ; EP 92 (87-95); LR+ 11,5 (7,3); LR-0.07 (0,03-0,15)) [19] or the study by Testa et al (SN 92,5 (89,6); EP 87,6 (83,5-90,7); LR+ 7,44 0,09; LR-70,7 (51,7-96,5) [27]. The three-step strategy can be used for triage at primary care or unspecialized centers by gynecologists with basic gynecologic ultrasound skills, thus reducing the number of patients referred to gynecological ultrasound units for expert assessment [27].…”
Section: Commentmentioning
confidence: 99%
“…This performance could be further improved by tutoring from medical practitioners who are experts in gynecological ultrasound [16]. M a n u s c r i p t Although this was a small series, the results were consistent with larger studies that use Descriptors + Rules + Expert: Sayasneh et al ; EP 92 (87-95); LR+ 11,5 (7,3); LR-0.07 (0,03-0,15)) [19] or the study by Testa et al (SN 92,5 (89,6); EP 87,6 (83,5-90,7); LR+ 7,44 0,09; LR-70,7 (51,7-96,5) [27]. The three-step strategy can be used for triage at primary care or unspecialized centers by gynecologists with basic gynecologic ultrasound skills, thus reducing the number of patients referred to gynecological ultrasound units for expert assessment [27].…”
Section: Commentmentioning
confidence: 99%
“…In their study, the detection of malignancy did not increase using HE4 and ROMA when compared with CA-125 alone. Testa et al 19 used a meta-analysis approach to centre-specific data during IOTA phase 3, and reported that the AUC pertaining to LR1, LR2, subjective assessment and RMI, was 0.93, 0.92, 0.91 and 0.88, respectively. There was sensitivity of 67% and specificity of 91% using the RMI.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Due to the diagnosis rate for early-stage ovarian cancer through single method is not high, combinative application is often needed. [50,51] However, the economic burden on patients is increased.…”
Section: Traditional Diagnostic Approaches For Ovarian Cancermentioning
confidence: 99%